2012
DOI: 10.1371/journal.pgen.1002941
|View full text |Cite
|
Sign up to set email alerts
|

MOV10 RNA Helicase Is a Potent Inhibitor of Retrotransposition in Cells

Abstract: MOV10 protein, a putative RNA helicase and component of the RNA–induced silencing complex (RISC), inhibits retrovirus replication. We show that MOV10 also severely restricts human LINE1 (L1), Alu, and SVA retrotransposons. MOV10 associates with the L1 ribonucleoprotein particle, along with other RNA helicases including DDX5, DHX9, DDX17, DDX21, and DDX39A. However, unlike MOV10, these other helicases do not strongly inhibit retrotransposition, an activity dependent upon intact helicase domains. MOV10 associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
244
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(273 citation statements)
references
References 95 publications
15
244
2
Order By: Relevance
“…1D), although compared with wild type MOV10, the inhibition activity of MOV10 (EQ) was markedly attenuated. Similar to our findings, Goodier et al (55) reported that similar mutations in the GKT and the DEAG motifs abolished anti-LINE-1 activity of MOV10. These results collectively indicate that the helicase motifs of MOV10 are required for suppressing the replication of LINE-1 and IAP.…”
Section: Mov10 Overexpression Diminishes Line-1 Retrotransposition-supporting
confidence: 92%
See 2 more Smart Citations
“…1D), although compared with wild type MOV10, the inhibition activity of MOV10 (EQ) was markedly attenuated. Similar to our findings, Goodier et al (55) reported that similar mutations in the GKT and the DEAG motifs abolished anti-LINE-1 activity of MOV10. These results collectively indicate that the helicase motifs of MOV10 are required for suppressing the replication of LINE-1 and IAP.…”
Section: Mov10 Overexpression Diminishes Line-1 Retrotransposition-supporting
confidence: 92%
“…studies (55)(56)(57). Because the transcription activity of LINE-1 promoter is not evidently affected by MOV10 (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Goodier et al first reported the localization of LINE-1 RNP components with stress granule markers. 38 [24][25][26] co-localize with LINE-1 RNP in stress granules or P-bodies (Fig. 1).…”
mentioning
confidence: 96%
“…[19][20][21][22][23] An RNA helicase MOV10 inhibits retrotransposition of LINE-1 by associating with LINE-1 RNP and diminishing LINE-1 RNA level. [24][25][26] A recent study by Goodier et al tested a panel of viral restriction factors and showed that many of them, including BST-2, ISG20, MAVS, Mx2 and ZAP, strongly reduce LINE-1 activity. 27 The anti-LINE-1 activity of ZAP was also reported by Moran group.…”
mentioning
confidence: 99%